Analysis of seed-germination in Piptadenia-Gonoacantha (Mart) MACBR (Leguminosae Mimosoideae) - Leite, ITD; Takaki, M. (Inst Tecnologia Parana, 1994)
Preliminary tests indicated 20-degrees-25-degrees-C as optimum temperature range to the germination of the seeds of P. gonoacantha. Seeds germinate both under light and dark conditions, although final percentage is always higher in latest condition. The transmission spectrum of the tegument was investigated and showed an enrichment of the light in far-red region which reaches the embryo. Consequently the white light inhibits partially germination. Another factor controlling germination was the water availability. Our results indicated that the excessive water available during imbibition inhibits the germination process. According to our results we propose that this species do not have a pioneer behavior and even though P. gonoacantha had been described as a riparian vegetation species, the germination process is strongly inhibited with excessive water during imbiibition process.
Keywords: PIPTADENIA-GONOACANTHA; SEED GERMINATION; LIGHT; TEMPERATURE; WATER AVAILABILITY